Abnormal, Error-Prone Bypass of Photoproducts by Xeroderma Pigmentosum Variant Cell Extracts Results in Extreme Strand Bias for the Kinds of Mutations Induced by UV Light - McGregor, W. Glenn (American Society for Microbiology, 1999)
Xeroderma pigmentosum (XP) is a rare genetic disease characterized by a greatly increased susceptibility to sunlight-induced skin cancer. Cells from the majority of patients are defective in nucleotide excision repair. However, cells from one set of patients, XP variants, exhibit normal repair but are abnormally slow in replicating DNA containing UV photoproducts. The frequency of UV radiation-induced mutations in the XP variant cells is significantly higher than that in normal human cells. Furthermore, the kinds of UV-induced mutations differ very significantly from normal. Instead of transitions, mainly C→T, 30% of the base substitutions consist of C→A transversions, all arising from photoproducts located in one strand. Mutations involving cytosine in the other strand are almost all C→T transitions. Forty-five percent of the substitutions involve thymine, and the majority are transversions. To test the hypothesis that the UV hypermutability and the abnormal spectrum of mutations result from abnormal bypass of photoproducts in DNA, we compared extracts from XP variant cells with those from HeLa cells and a fibroblast cell strain, MSU-1.2, for the ability to replicate a UV-irradiated form I M13 phage. The M13 template contains a simian virus 40 origin of replication located directly to the left or to the right of the target gene, lacZα, so that the template for the leading and lagging strands of DNA replication is defined. Reduction of replication to ∼37% of the control value required only 1 photoproduct per template for XP variant cell extracts, but ∼2.2 photoproducts for HeLa or MSU-1.2 cell extracts. The frequency of mutants induced was four times higher with XP variant cell extracts than with HeLa or MSU-1.2 cell extracts. With XP variant cell extracts, the proportion of C→A transversions reached as high as 43% with either M13 template and arose from photoproducts located in the template for leading-strand synthesis; with HeLa or MSU-1.2 cell extracts, this value was only 5%, and these arose from photoproducts in either strand. With the XP variant extracts, 26% of the substitutions involved thymine, and virtually all were T→A transversions. Sequence analysis of the coding region of the catalytic subunit of DNA polymerase delta in XP variant cell lines revealed two polymorphisms, but these do not account for the reduced bypass fidelity. Our data indicate that the UV hypermutability of XP variant cells results from reduced bypass fidelity and that unlike for normal cells, bypass of photoproducts involving cytosine in the template for the leading strand differs significantly from that of photoproducts in the lagging strand.